The Effect of Clarity of Budget Targets, Accounting Control and Reporting System on The Performance Accountability - Elpisah, E.; Suarlin, S. (Manunggal Halim Jaya, 2022)
This research aims to (1) understand the impact of a clear target budget on the accountability performance of the agency government in district Sinjai and (2) understand the impact of control accounting on the accountability performance of the agency government in district Sinjai. (3) understand the influence system reporting to the accountability performance agency government in the Sinjai district. This was studied using primary data from questionnaires distributed to 86 employees from the 43 SKPD. This study uses method analysis, multiple linear regression, and data analysis using the SPSS 21 program. The findings indicate that: (1) a clear target budget significantly influences the level of accountability performance of agency government. (2) Control accounting has had a positive impact; however, there must be indicators of the level of accountability performance of agency government. (3) Budget influences on system reporting significantly impact the agency government's level of accountability performance. This means that the more precise the target budget, control accounting, and system reporting budget are, the better the accountability performance of the agency government in the District of Sinjai will be.